The Contribution of Leg Muscle Explosive Power and Strength to Long Jump Ability in USK Physical Education Students Class of 2022 - Muhammad Iqbal; Syamsulrizal Syamsulrizal; Mansur Mansur; Nofri Naldo; Dibra Farras Fahima; Iswanda Suryanullah (Departement of Mathematics Education, 2024)
This study is entitled